Approaches to Definition of Key Functions and Target Indicators of Regional Research and Educational Centers - N. G. Kurakova; O. V. Cherchenko (Ekonomika Nauki)
An overview of the tested in the Russian Federation in 2009–2018 is presented. Models of cooperation between organizations of science, education and industrial partners: Resolutions of the Government of the Russian Federation of April 9, 2010 No. 218, Federal law of August 2, 2009 No. 217-FZ, aimed at creating a ring of small innovative enterprises around universities, as well as the project of the Association of Entrepreneurial universities. It is proposed to be guided by the understanding of the criteria for technological development, which is proposed by the strategic planning documents, when determining the key functions of scientific and educational centers (SEC). The assumption is made that formalizing this concept would allow developing a more harmonious system of indicators of the technological development of the country as a whole and individual regions and more clearly formulating the goals and objectives of SEC as a model of technological development. It is noted that the SEC efficiency indicators proposed by the methodology of The Ministry of Science and Higher Education of the Russian Federation to a greater extent reflect the totality of the functions of the cooperation participants, but not the quality of initiatives aimed at accelerating the technological development of the region. The basic conditions for productive cooperation are proposed to include the critical mass of specialized companies, ensuring the dominance of private initiative, attracting and retaining highly qualified specialists from scientific and business circles, as well as venture investors.